KEPEMIMPINAN RIDWAN KAMIL DI KOA BANDUNG TAHUN 2013-2018 : KAJIAN INOVASI KEBIJAKAN KEPEMIMPINAN ADAPTIF - Dewi Pitriyanti; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
The study of innovation is a requirement not only for private but also public organizations. The pattern of recruitment of leadership in the region through general elections, provides opportunities for various groups to provide ideas through work programs offered to the people. One of the leaders who was able to change the face of the region through policy innovation was Ridwan Kamil. This study aims to know how the leadership pattern of Ridwan Kamil was carried out so can produce policy innovation. The method of this research is qualitative method with data collection through interviews, documentation and observation. The results of this study indicate that there are three main forms of innovation in the leadership of Ridwan Kamil, those are Bandung Smart City, the Development Innovation and Regional Empowerment Program (PIPPK) and Relocation of Stree Vendors. The success of these innovations can not be separated from the role of Ridwan Kamil as Mayor of Bandung who is able to implement adaptive leadership steps based on four parameters, namely directing subordinates to the new environment, leading with empathy, learning throght self corrections and being able to create win win solutions. Problems related to the agent structure and accountability that are generally faced by political leaders are able to be utilized by Ridwan Kamil to produce innovative policies in Bandung because of their dynamic. Keywords: Leadership, Innovative Policy, Bandung Smart City, PIPPK and the relocation of street vendors